Novel Insights Into Leishmania (Viannia) braziliensis In Vitro Fitness Guided by Temperature Changes Along With Its Subtilisins and Oligopeptidase B - Zabala-Peñafiel, Anabel; Cysne-Finkelstein, Lea; Conceição-Silva, Fatima; Fagundes, Aline; Miranda, Luciana de Freitas Campos; Souza-Silva, Franklin; Brandt, Artur A. M. L.; Dias-Lopes, Geovane; Alves, Carlos Roberto (Frontiers in Cellular and Infection Microbiology, 2022)
Proteases are virulence factors with a recognized impact on the Leishmania spp. life cycle. This study considers a set of analyses measuring phenotypic factors of L. (V.) braziliensis clinical isolates as promastigotes growth curves, murine peritoneal macrophages infection, inflammatory mediators production, and serine proteases gene expression (subtilisin 13: S13, subtilisin 28: S28, oligopeptidase B: OPB) assessing these isolates’ fitness on in vitro conditions. Parasites had different behavior during the early growth phase from day zero to day three, and all isolates reached the stationary growth phase between days four and seven. Macrophages infection showed two tendencies, one of decreased infection rate and number of parasites per macrophage (Infection Index <1000) and another with a constant infection index (≥1400). TNF-α (≥10 pg/mL) detected in infections by 75% of isolates, IL-6 (≥80 pg/mL) by 30% of isolates and low levels of NO (≥0.01µM) in almost all infections. Gene expression showed higher values of S13 (≥2RQ) in the intracellular amastigotes of all the isolates evaluated. On the contrary, S28 expression was low (≤1RQ) in all isolates. OPB expression was different between promastigotes and intracellular amastigotes, being significantly higher (≥2RQ) in the latter form of 58% of the isolates. Predictive structural assays of S13 and OPB were performed to explore temperature influence on gene expression and the encoded proteases. Gene expression data is discussed based on in silico predictions of regulatory regions that show plasticity in the linearity index of secondary structures of S13 and OPB 3’-untranslated regions of mRNA, dependent on temperature changes. While hairpin structures suggest an active region of mRNA for both genes above 26°C, pseudoknot structure found in S13 is an indication of a particular profile of this gene at mammalian host temperatures (37°C). Furthermore, the predicted 3D structures are in accordance with the influence of these temperatures on the catalytic site stability of both enzymes, favoring their action over peptide substrates. Data gathered here suggest that L. (V.) braziliensis serine proteases can be influenced by the temperature conditions affecting parasite fitness throughout its life cycle.